Green Marketing and Market Efficiency: Consumer Behaviour and the Risks of Greenwashing (European Journal of Marketing and Economics, 2026)
This study examines how sustainability-oriented marketing practices influence consumer-related outcomes, with particular attention to trust formation, purchasing decisions, and long-term market functioning. Based on a critical review of recent academic literature, the article analyses the role of credibility and transparency in sustainability communication and their implications for economic efficiency. The findings indicate that authentic and verifiable sustainability claims strengthen consumer confidence by reducing information asymmetry and improving the reliability of market signals. In contrast, misleading environmental communication undermines credibility, distorts competitive conditions, and weakens incentives for genuine sustainable innovation. By integrating perspectives from marketing theory and economic analysis, the study highlights trust as a key mechanism linking sustainability communication to consumer decision-making and efficient resource allocation. The article contributes to the literature by framing deceptive sustainability practices not only as an ethical concern but also as a structural threat to well-functioning markets, with implications for managers and policymakers seeking to promote credible and resilient sustainability-driven economic systems.
Keywords: Sustainability communication; Brand trust; Information asymmetry; Ethical marketing; Circular economy; Consumer decision-making